2003
DOI: 10.1021/jp034548e
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids of Chelated Orthoborates as Model Ionic Glassformers

Abstract: Ionic liquids based on various chelated orthoborate anions of different N-containing onium cations have been synthesized using an economic synthesis strategy. Most orthoborates do not crystallize. They are found to have much higher glass transition temperatures and room-temperature viscosities than those with perfluorinated anions such as TFSI-, BF4 -, and CF3SO3 - (Tf-), as predicted from anion polarizability arguments. The ambient conductivities of the new ionic liquids are low relative to those with perfluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
153
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(167 citation statements)
references
References 34 publications
12
153
1
Order By: Relevance
“…62,63 Despite the decrease of the electrostatic interactions, the pyridinium based ionic liquids have been found to be associated with a higher cohesion than the imidazolium ionic liquids, which is associated to the importance of cation-cation dispersive interactions. 64,65 The molecular interactions between the ions and their structural arrangement results in a complex structural/ nanostructural organization and hence interesting properties. Therefore, the knowledge of the dependence of ionic liquids properties on their molecular structures is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…62,63 Despite the decrease of the electrostatic interactions, the pyridinium based ionic liquids have been found to be associated with a higher cohesion than the imidazolium ionic liquids, which is associated to the importance of cation-cation dispersive interactions. 64,65 The molecular interactions between the ions and their structural arrangement results in a complex structural/ nanostructural organization and hence interesting properties. Therefore, the knowledge of the dependence of ionic liquids properties on their molecular structures is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…The density (ρ) of ionic liquids (ILs) decreases with the increase in organic cation bulkiness and anion selection affects ILs' density. Normally, the density of ILs varies in the range of 1.05-1.36 g/cm 3 at ambient temperature [43,44]. In terms of ILs' thermal stability, a research conducted had observed that thermal stability was dependent on both the cation and the anion of ILs.…”
Section: Physicochemical Properties Of Imidazolium-based Ionic Liquidsmentioning
confidence: 99%
“…Thus, the liquid structures of RTILs are determined by a balance between long-range electrostatic forces and local geometric factors. As a result, many RTILs can be easily supercooled and form the glassy state [5][6][7]. Changes in the cation and anion combinations allow the physical and chemical properties of ionic liquids to be effectively tuned, for example, for manipulating the solvent properties of RTILs in order to achieve different purposes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%